2022
DOI: 10.1186/s12885-022-09307-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning identifies Acute Promyelocytic Leukemia in bone marrow smears

Abstract: Background Acute promyelocytic leukemia (APL) is considered a hematologic emergency due to high risk of bleeding and fatal hemorrhages being a major cause of death. Despite lower death rates reported from clinical trials, patient registry data suggest an early death rate of 20%, especially for elderly and frail patients. Therefore, reliable diagnosis is required as treatment with differentiation-inducing agents leads to cure in the majority of patients. However, diagnosis commonly relies on cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 45 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…Congruent with the response pattern from the previous answers, the category "Improved diagnostic confidence" received the greatest level of support. This is in line with the above-mentioned assumption that AI applications are already being used to some extent in the clinic, particularly for diagnostic procedures (2, 3,5,6,28) and are therefore much more widely accepted among surgeons than other AI tools. However, survey participants also see great potential in AI to facilitate "More precise and minimally invasive surgical techniques, " which was the second most selected use case.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Congruent with the response pattern from the previous answers, the category "Improved diagnostic confidence" received the greatest level of support. This is in line with the above-mentioned assumption that AI applications are already being used to some extent in the clinic, particularly for diagnostic procedures (2, 3,5,6,28) and are therefore much more widely accepted among surgeons than other AI tools. However, survey participants also see great potential in AI to facilitate "More precise and minimally invasive surgical techniques, " which was the second most selected use case.…”
Section: Discussionsupporting
confidence: 83%
“…In pathology, Eckhardt et al developed an AI program that could distinguish between AML samples and healthy controls based on bone marrow images with a very high sensitivity and specificity. Moreover, with the help of this AI application it was possible to predict with high probability the presence of one of the most common mutations in AML based on cytomorphological features alone (5).…”
Section: Introductionmentioning
confidence: 99%
“…genetics, cytochemistry, flow cytometry). An equally important drawback of previous fully supervised models 7,9,13,16,17 is that they require hundreds of thousands of object-level cell annotations provided by human experts 18 which are not only difficult to obtain at scale but are also susceptible to inconsistencies due to the subjectivity and cognitive fatigue of annotators. To overcome these limitations and, to provide a clinically…”
Section: Detection Of Acute Promyelocytic Leukemia In Peripheral Bloo...mentioning
confidence: 99%
“…genetics, cytochemistry, flow cytometry). An equally important drawback of previous fully supervised models 7 , 9 , 13 , 16 , 17 is that they require hundreds of thousands of object-level cell annotations provided by human experts 18 which are not only difficult to obtain at scale but are also susceptible to inconsistencies due to the subjectivity and cognitive fatigue of annotators. To overcome these limitations and, to provide a clinically relevant system that could support, together with clinical evaluation and ancillary laboratory parameters, the prompt treatment in APL cases, we designed a Multiple Instance Learning for Leukocyte Identification (MILLIE) approach.…”
Section: Introductionmentioning
confidence: 99%
“…The testing findings demonstrated that the method proposed achieved a precision of (98.3%). Eckardt JN et al [20]suggested a multi-stage DL framework in another DL study to detect acute promyelocytic leukemia (APL) only from bone marrow smear pictures. They examined a small medical dataset of 51 APL patients and contrasted it with samples from 236 normal bone marrow donors and 1048 AML patients who did not have APL.…”
Section: Literature Reviewmentioning
confidence: 99%